أثر بيئة العمل التنظيمية في مشاعر الاغتراب الوظيفي لدى معلمي التعليم الثانوي لدراسة تجريبية في مدينة العجيلات (Comprehensive Journal of Science, 2025)
This research aims to examine the causal relationship between the organizational work environment and job alienation among secondary school teachers in the city of Ajilat, Libya, it does so by testing the impact of six key dimensions of the organizational work environment: salaries and financial incentives, relationships with students, relationships with colleagues, use of technology, participation in decision-making, and performance evaluation, on the five dimensions of job alienation (loss of meaning, loss of power, loss of norms, social isolation, and self- estrangement).The descriptive analytical method was employed, and a questionnaire was distributed to a simple random sample of 218 male and female teachers out of a total of 250 forms distributed. Statistical analysis using multiple regression coefficients revealed that the first three dimensions salaries and incentives, relationships with colleagues, and use of technology collectively explained 52.4% of the variance in job alienation, while the remaining dimensions contributed additional explanatory power percentages ranging between 13.6% and 14.6%. The overall mean of job alienation reached 3.72 out of 5, indicating a noticeable rise in negative feelings tow artwork. The Study recommends restructuring reward systems, fostering a culture of teamwork, investing in technological infrastructure, and providing genuine channels for participation in decision-making, in addition to conducting longitudinal studies to assess the impact of organizational interventions.